Leadership in administration a sociological interpretation - Selznick, Philip (University of California Press, 1984)
An essay that outlines a perspective for the study of leadership in administrative organizations. It was written in the conviction that more reflective, theoretical discussion is needed to guide the gathering of facts that the diagnosis of troubles.